Social media analysis on Malaysian youth participation in Sustainable Development Goals (SDGs) activities / Mohd Idham Mohd Yusof ... [et al.] - Mohd Yusof, Mohd Idham; Tuan Ismail, Tuan Nooriani; Ab Rahman, Farah Adilla; Yusof, Radduan; Mohd Zain, Muhammad Aiman (2022)
Youth participation in the execution of Sustainable Development Goals (SDGs) has been emphasised by international entities such as the United Nations (UN) and is being discussed academically. As an emerging populace group which would be affected by prevailing decisions on sustainable development, they are termed as one of the Major Groups and Other Stakeholders (MGoS) in the SDGs. This study aims to look at youth's participation and inclusion in SDG-related activities in Malaysia, specifically in meeting the three core sustainability principles - economic, social, and environmental. This study employed qualitative and quantitative approaches through social media analysis and a survey. Three youth associations were purposefully chosen, and their engagement in SDG-related initiatives was assessed by examining their social media presence. Furthermore, 238 youth from Malaysia were polled on-line to get responses on the most successful ways to promote the SDGs. This study found that SDGs linked to economic, social, and environmental, have been prioritised by the selected youth associations. The social media analysis concluded that these youth's SDG-related initiatives aimed to fulfil SDG11 on establishing "sustainable cities and communities". The descriptive study also noted that Malaysian youth are inclined towards learning about SDGs and their underlying ideas through mass media, social media, and the education system. The conclusions of this study are not generalisable. Nonetheless, it offers unique insights into the progress of SDGs in Malaysia due to youth participation and enriches the existing literature within the context of sustainable development. More extensive youth categories, according to survey respondents, will be required in future works. The SDGs' knowledge and partaking among youth in educational institutions and employed youth can also be investigated further.